2023
DOI: 10.1088/1367-2630/acf33c
|View full text |Cite
|
Sign up to set email alerts
|

Dirac signal processing of higher-order topological signals

Lucille Calmon,
Michael T Schaub,
Ginestra Bianconi

Abstract: 
Higher-order networks can sustain topological signals which are variables associated not only to the nodes, but also to the links, to the triangles and in general to the higher dimensional simplices of simplicial complexes. These topological signals can describe a large variety of real systems including currents in the ocean, synaptic currents between neurons and biological transportation networks.
In real scenarios topological signal data might be noisy and an important task is to process th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The topological Dirac operator can also be used to characterize the dynamics of coupled (classical) topological signals [81]. In particular the Dirac operator allows to define a new class of dynamical processes on network and simplicial complexes, revealing new physical phenomena as demonstrated by its application to Dirac synchronization, Dirac Turing patterns and Dirac signal processing [338][339][340][341].…”
Section: Quantum Concepts Useful For Complex Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…The topological Dirac operator can also be used to characterize the dynamics of coupled (classical) topological signals [81]. In particular the Dirac operator allows to define a new class of dynamical processes on network and simplicial complexes, revealing new physical phenomena as demonstrated by its application to Dirac synchronization, Dirac Turing patterns and Dirac signal processing [338][339][340][341].…”
Section: Quantum Concepts Useful For Complex Networkmentioning
confidence: 99%
“…Another inference algorithm using the Dirac operator is Dirac signal processing [341] that allows to jointly process signals defined on simplices of different dimensions.…”
Section: Quantum Higher-order Network and The Topological Dirac Operatormentioning
confidence: 99%
“…The investigation of the dynamical state of simplicial complexes has instead revealed that this is only a special case and that in general each simplex (higher-order interaction) can be associated with a dynamical variable leading to the notion of topological signals. This change of paradigm has lead to novel understanding of topological synchronization [30][31][32][33][34] and higher-order diffusion dynamics [35][36][37][38] and to novel signal processing [39][40][41] and topological neural network algorithms [42,43]. In particular, higher-order diffusion dynamics is among the most basic topological dynamical processes, describing diffusion from n-dimensional simplices to n-dimensional simplices going either one dimension up or one dimension down.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, growing attention is addressed to the discrete topological Dirac operator [1,2], originally introduced in non-commutative geometry [3][4][5][6][7], and then used in quantum graphs [8][9][10][11][12][13][14][15] and in network theory [16][17][18][19][20][21]. On a network, the discrete topological Dirac operator is defined over topological spinors, which are the direct sum of zero-cochain and one-cochains.…”
Section: Introductionmentioning
confidence: 99%